Sonographic pattern of fetal head descent: relationship with duration of active second stage of labor and occiput position at delivery. (28th May 2014) - Ghi, T.; Maroni, E.; Youssef, A.; Morselli‐Labate, A. M.; Paccapelo, A.; Montaguti, E.; Rizzo, N.; Pilu, G.
ABSTRACT Objectives The objectives of this study were firstly to assess the longitudinal changes of various sonographic parameters of fetal head progression in relation to length of active second stage of labor, and secondly to compare ultrasound findings obtained longitudinally among fetuses with persistent occiput posterior (OP) vs those with persistent occiput anterior (OA) position. Methods From a series of nulliparous low‐risk women at term attending the labor ward of our university hospital, transperineal ultrasound volumes were prospectively acquired at the beginning of the active second stage (T1) and at 40‐min intervals thereafter until delivery (T2, T3). Sonographic parameters were derived from offline analysis of each volume, including the angle of progression (AoP), progression distance (PD), head–symphysis distance (HSD), head direction (HD) and midline angle. These parameters were compared between patients who delivered within 60 min from the beginning of the active second stage of labor (early delivery) and those who remained undelivered by that time (late delivery). Fetal head position was determined from stored digital images of transabdominal examinations performed at the beginning of the active second stage. Comparison was performed between fetuses with OA and those with persistent OP position at delivery. Results Spontaneous vaginal delivery was achieved in 58 (81.7%) cases, whereas vacuum extraction and Cesarean section were performed in eight (11.3%) and five (7.0%) cases, respectively. Delivery was achieved within 60 min from the beginning of the active second stage in 44 (62.0%) patients. In the early vs late delivery groups, measurements of AoP, HSD and PD at T1 were significantly different (AoP, 143.9 ± 20.5° vs 125.3 ± 15.0°, P < 0.001; HSD, 14.8 ± 4.5 mm vs 20.9 ± 5.8 mm, P < 0.001; PD, 44.0 ± 14.1 vs 35.0 ± 13.1 mm, P = 0.008). On logistic regression analysis of data obtained at T1, maternal body mass index, oxytocin administration, neonatal birth weight and HSD appeared to predict independently duration of the active second stage. Among fetuses delivering in the OP position (n = 10, 13.5%), Cesarean delivery was significantly more common than in those delivering in the OA position (n = 5 (50.0%) vs n = 2 (3.1%), P = 0.001). Women with persistent OP position compared with OA showed a significantly different AoP at T1 (122 ± 17° vs 138 ± 20°, P = 0.016), HD and HSD at T1 (HD, 112 ± 17 mm vs 86 ± 19 mm, P < 0.001; HSD, 16.5 ± 5.4 mm vs 22.8 ± 6.6 mm, P = 0.008) and at T2 (HD, 120 ± 16 vs 82 ± 27 mm, P = 0.008; HSD, 12.6 ± 3.4 mm vs 18.5 ± 5.4 mm, P = 0.038). Conclusions AoP, PD and HSD are significantly different between patients undergoing delivery before or after 60 min from the beginning of the active second stage of labor. Ultrasound parameters are among the significant predictors of duration of the active second stage. Moreover, in fetuses persisting in the OP position vs those delivering in the OA position, fetal head progression seems to differ at early phases of the active second stage. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.